Pengembangan Media Pembelajaran Berbasis Flipbook Interaktif Pada Materi Sel Siswa Kelas XI SMA N 01 Kotagajah - Sinta Ayu Dewi; Hifni Septina Carolina (Quagga: Jurnal Pendidikan dan Biologi, 2024)
21st century education requires teachers to be able to utilize technological advances and be more innovative in providing media to support learning activities. In fact, the use of media in the learning process has not been varied and interactive for students. The purpose of the research conducted is to produce an Interactive Flipbook-based learning media on cell material for class XI SMA N 01 Kotagajah students that is feasible to use. This research uses the research and development method, namely Research and Development (R&D) the development model used is the ADDIE model which has five stages, namely: analysis, design, development, implementation, and evaluation. The results of the study showed that the results of validation on material experts obtained a percentage of 88% and media experts reached a percentage of 92% with very feasible criteria, this was supported by the results of responses by teachers who obtained a percentage of 90% in the "very good" category and students got a percentage of 84% in the good category. It can be stated that the Interactive Flipbook-based learning media on cell material for class XI SMA N 01 Kotagajah is very feasible to use.